Roofer: An Engineered Management System (EMS) for Bituminous Built-Up Roofs - Bailey, David M.; Brotherson, Donald E.; Tobiasson, Wayne; Knehans, Al (Building Research Council. School of Architecture. College of Fine and Applied Arts. University of Illinois at Urbana-Champaign, 2014)
Each of the U.S. anned services branches has a very large inventory of roofs with bituminous built-up membranes. Roof repairs and reconstruction are steadily increasing as the roofs approach the end of their service lives, making it increasingly important to better manage maintenance funds. Currently, there is need for a systematic procedure to detennine priorities and select repair strategies that will ensure a maximum return on investment. In response to this problem, the U.S. Anny Construction Engineering Research Laboratory (USACERL), with the assistance of the U.S. Army Cold Regions Research and Engineering Laboratory (USACRREL) and the U.S. Anny Engineering and Housing Support Center (USAEHSC), has developed ROOFER, a roofing maintenance management system. ROOFER provides military installations with a practical decision-making procedure to identify problems and select maintenance and repair strategies for roofs with bituminous membranes. U.S. Army Corps of Engineers Construction Engineering Research Laboratory